Effect of the waste from disassembling import waste electrical equipment on the aerobic treatment of refuse leachate - FANG Cheng-ran; SHEN Dong-sheng (浙江大学学报. 农业与生命科学版)
The effect of the waste from disassembling import waste electrical equipment on the aerobic treatment of refuse leachate was studied by testing the concentrations of CODcr, Cu, Zn, Ni and oil in inlet and outlet of leachate. The results showed that the effect of the aerobic treatment on CODCr and oil of leachate did not generally change provided the amount of the wastes from disassembling import waste electrical equipment was less than amount of municipal refuse. But CODCr, oil and the metal content of the water in outlet were all higher than that of the first grade of waste discharge as required by the National Standard. So the net result of such treatment was enhancement of metal accumulation in the activiated sludge, which ultimately led to unfavorable impact on its biological activity.